(untitled) (Research, Society and Development, 2021)
Introduction: The treatment of diseases caused by enterobacteria is an increasing challenge. This problem results from the inefficiency of antibiotics to fight pathogens or to stimulate phagocytosis of cells of the reticuloendothelial system, mainly against bacteria that install and multiply inside phagocytic cells. Some antibiotics are ineffective at entering cells or have their capacity reduced by the plasma membrane. Thus, the scientific community joins efforts seeking new therapeutic alternatives that overcome these limitations. Liposomes are lipid nanocarriers capable of encapsulating antibiotics, aiming at increasing the specificity of delivery, the concentration of compounds delivered to the site, maintaining the plasma concentration of drugs and protecting the active molecules. Thus, the objective of this review was to describe the main liposomal properties, emphasizing the advantages of using these lipid vesicles to administer antibiotics against infections caused by enterobacteria. Methodology: This is a bibliographic review through searches in national and international electronic databases, selecting articles from 2007 to 2020 using the descriptors: Gram-negative bacteria, bacterial resistance, antimicrobials and nanotechnology. Results: Cationic and furtive liposomes consisting mainly of cholesterol, PEG, phosphatidylcholine and carboxymethyl chitosan encapsulating drugs such as amoxicillin, ciprofloxacin, cloxacillin, vancomycin, azithromycin, amoxicillin, cefepime, gentamicin and cefotaxime have shown antibacterial activity. Liposomes encapsulating drugs such as chloramphenicol, azithromycin, gentamicin and polymyxin B showed greater antibiofilm efficiency compared to enterobacteria when compared to non-encapsulated drugs. Conclusion: The results showed that liposomes have significant therapeutic potential for the treatment of infections caused by enterobacteria.